Foreign language learning problems of students classified as learning disabled and non-learning disabled: is there a difference? - Sparks RL (Topics in Language Disorders, 2001)
Research on students with foreign language (FL) learning problems is reviewed. The Linguistic Coding Differences Hypothesis, a theory explaining FL learning problems, is described. The continuum of FL learning is explained and the primary role of linguistic variables in FL learning is supported. Recent research on students classified as LD with FL learning problems is also reviewed. A recent court decision regarding FL course substitutions, the Boston University case, is discussed. Implications of the research and court case for professionals and educators are presented. Copyright © 2001 by Aspen Publishers, Inc.